QASports: A Question Answering Dataset about Sports - Jardim, Pedro Calciolari; Moraes, Leonardo Mauro Pereira; Aguiar, Cristina Dutra (Anais do Dataset Showcase Workshop (DSW); 2023: Anais do V Dataset Showcase WorkshopDO - 10.5753/dsw.2023.233602, 2023)
Sport is one of the most popular and revenue-generating forms of entertainment. Therefore, analyzing data related to this domain introduces several opportunities for Question Answering (QA) systems, such as supporting tactical decision-making. But, to develop and evaluate QA systems, researchers and developers need datasets that contain questions and their corresponding answers. In this paper, we focus on this issue. We propose QASports, the first large sports question answering dataset for extractive answer questions. QASports contains more than 1.5 million triples of questions, answers, and context about three popular sports: soccer, American football, and basketball. We describe the QASports processes of data collection and questions and answers generation. We also describe the characteristics of the QASports data. Furthermore, we analyze the sources used to obtain raw data and investigate the usability of QASports by issuing "wh-queries". Moreover, we describe scenarios for using QASports, highlighting its importance for training and evaluating QA systems.